2013
DOI: 10.1111/jipb.12002
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of a Glycine max Degradome Library Identify microRNA Targets and MicroRNAs that Trigger Secondary SiRNA Biogenesis

Abstract: Plant microRNAs (miRNAs) regulate gene expression mainly by guiding cleavage of target mRNAs. In this study, a degradome library constructed from different soybean (Glycine max (L.) Merr.) tissues was deep-sequenced. 428 potential targets of small interfering RNAs and 25 novel miRNA families were identified. A total of 211 potential miRNA targets, including 174 conserved miRNA targets and 37 soybean-specific miRNA targets, were identified. Among them, 121 targets were first discovered in soybean. The signature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 67 publications
(127 reference statements)
2
28
0
Order By: Relevance
“…The functional significance of TAS3a-c loci in leaf polarity specification and morphogenesis has been established [7], and is suggested for TAS1a-c/2 as a means of dosage compensation by network repression of the large family of PENTATRICOPEPTIDE REPEAT genes in Arabidopsis ( Arabidopsis thaliana ) [8]. The functions of novel TAS candidates in rice ( Oryza sativa ) [911], soybean ( Glycine max ) [12], grape [13], tobacco ( Nicotiana tabacum ) [14, 15], and Norway spruce ( Picea abies ) [16] are not known. TAS loci, like MIRNA genes, have evolved independently at different times [17], and the derived tasiRNAs share some biosynthetic steps with miRNAs [18].…”
Section: Functions Of Tas Locimentioning
confidence: 99%
“…The functional significance of TAS3a-c loci in leaf polarity specification and morphogenesis has been established [7], and is suggested for TAS1a-c/2 as a means of dosage compensation by network repression of the large family of PENTATRICOPEPTIDE REPEAT genes in Arabidopsis ( Arabidopsis thaliana ) [8]. The functions of novel TAS candidates in rice ( Oryza sativa ) [911], soybean ( Glycine max ) [12], grape [13], tobacco ( Nicotiana tabacum ) [14, 15], and Norway spruce ( Picea abies ) [16] are not known. TAS loci, like MIRNA genes, have evolved independently at different times [17], and the derived tasiRNAs share some biosynthetic steps with miRNAs [18].…”
Section: Functions Of Tas Locimentioning
confidence: 99%
“…Such bulged bases, rather than miRNA-5p or miRNA-3p length, have been shown to be a critical factor for some 22-nucleotide miRNAs to trigger the production of secondary siRNAs (Manavella et al, 2012). The PARE data and small RNA data previously generated by our studies in soybean (Song et al, 2011;Shamimuzzaman and Vodkin, 2012;Hu et al, 2013;Arikit et al, 2014;Zhao et al, 2015) reveal that miR1510 targets the encoded, core P-loop motif of NB-LRRs, a sequence highly conserved among the 111 predicted targets in soybean (Figures 6C and 6D; Supplemental Figure 13). By contrast, the target sites of miR482 and miR2118 in NB-LRR are more diverged, to a level at which only a few NB-LRR copies could be targeted by these two interspecifically highly conserved miRNAs; as a result, NB-LRRs in soybean are primarily targeted by miR1510.…”
Section: The Peg Targets Of Conserved Mirnas Are More Preferentially mentioning
confidence: 99%
“…To understand whether the fractionation of duplicated MIRNAs may have shaped the pattern of retention and elimination of their miRNA targets following the recent WGD event in soybean, we selected and analyzed 289 miRNA targets that have been validated using three parallel analysis of RNA ends (PARE) libraries (Song et al, 2011;Shamimuzzaman and Vodkin, 2012;Hu et al, 2013;Arikit et al, 2014;Supplemental Figure 6). It was found that the 289 PEGs were targeted by 155 miRNAs generated from 265 MIRNAs, including 186 MIRNA duplicates and 79 MIRNA singletons.…”
Section: Functional Divergence Of Mirna Duplicates Reflected By Variamentioning
confidence: 99%
“…Soybean was the first legume species with a published high-quality draft genome sequence (Schmutz et al, 2010). Because miRNAs play an important regulatory role in a wide variety of developmental and metabolic processes in plants, more and more soybean miRNAs have been identified (Zhang et al, 2008;Chen et al, 2009;Wang et al, 2009;Guo et al, 2011;Kulcheski et al, 2011;Li et al, 2011;Song et al, 2011;Wong et al, 2011;Zeng et al, 2012;Hu et al, 2013), but the features of the upstream sequences of these miRNAs have not been comprehensively analyzed. Core promoters and cis-acting elements of 82 soybean miRNAs from the miRBase database were analyzed by bioinformatics methods (Liu et al, 2010), but this analysis involved a relatively small number of miRNA genes.…”
Section: Introductionmentioning
confidence: 99%
“…Core promoters and cis-acting elements of 82 soybean miRNAs from the miRBase database were analyzed by bioinformatics methods (Liu et al, 2010), but this analysis involved a relatively small number of miRNA genes. We have identified substantial numbers of miRNAs by deep sequencing of a Glycine max degradome library (Hu et al, 2013). In this study, the core promoters and cis-acting elements of those miRNAs were predicted by bioinformatics methods to reveal the features of the core promoters of soybean miRNAs.…”
Section: Introductionmentioning
confidence: 99%